2022
DOI: 10.3390/healthcare10081391
|View full text |Cite
|
Sign up to set email alerts
|

Patient-Reported Experiences and Satisfaction with Rural Outreach Clinics in New South Wales, Australia: A Cross-Sectional Study

Abstract: Introduction: Many studies have been conducted on how physicians view outreach health services, yet few have explored how rural patients view these services. This study aimed to examine the patient experience and satisfaction with outreach health services in rural NSW, Australia and the factors associated with satisfaction. Methods: A cross-sectional study was conducted among patients who visited outreach health services between December 2020 and February 2021 across rural and remote New South Wales, Australia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 51 publications
(67 reference statements)
1
1
0
Order By: Relevance
“…Together, these findings suggest that patients value the regional outreach service and provide support for ongoing provision of the service. The high levels of satisfaction are consistent with a 2022 study by Islam and colleagues, 11 in which 93% of participants were satisfied with the regional outreach services they utilised. Among the patients with cancer surveyed in this study, almost half reported at least one ongoing symptom or side effect of cancer.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…Together, these findings suggest that patients value the regional outreach service and provide support for ongoing provision of the service. The high levels of satisfaction are consistent with a 2022 study by Islam and colleagues, 11 in which 93% of participants were satisfied with the regional outreach services they utilised. Among the patients with cancer surveyed in this study, almost half reported at least one ongoing symptom or side effect of cancer.…”
Section: Discussionsupporting
confidence: 87%
“…In Australia, the Rural Doctor's Network (RDN) perform annual surveys of patients visiting outreach clinics to evaluate services and for quality improvement. Results from a survey administered by the RDN from December 2020 to February 2021 reported high satisfaction with services at the outreach clinics, with 93% of the 207 participants indicating they were satisfied, with behaviour of the health professional a strong predictor of overall patient satisfaction 11 . In New South Wales (NSW), the most populous state of Australia, the Bureau of Health Information (NSW BHI) began surveying patients on their experience of the public healthcare system in 2012 as part of the NSW Patient Survey Programme.…”
Section: Introductionmentioning
confidence: 99%